2014
DOI: 10.3892/mmr.2014.2366
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 induces epithelial-mesenchymal transition and increased expression of matrix metalloproteinase-16 via miR-200b downregulation in bladder cancer cells

Abstract: Transforming growth factor‑β1 (TGF‑β1) is involved in the migration and metastases of bladder cancer. The present study was designed to investigate whether TGF‑β1 is able to induce epithelial‑mesenchymal transition (EMT) and the upregulation of matrix metalloproteinase‑16 (MMP‑16), and to identify an association between EMT and MMP‑16 in bladder cancer. Following TGF‑β1 treatment, samples of HTB9 and T24 bladder cancer cells were collected at various time points. Western blotting and quantitative polymerase ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In fact, in a study focused on melanoma patients, a copy‐number gain or overexpression of MMP‐16 has been determined as a putative indicator of adverse melanoma prognosis, associated with poor clinical outcome, collagen bundle assembly around tumor cell nests, and lymphatic invasion (Tatti et al, ). Other studies have shown that tumor growth factor beta 1 can increase the levels of MMP‐16, eliciting a potential connection with the invasion and metastasis in bladder cancer (Chen et al, ). Some studies investigating the effects of inhibition of the metalloproteinase have reported promising data.…”
Section: Matrix Metalloproteinase‐16mentioning
confidence: 97%
“…In fact, in a study focused on melanoma patients, a copy‐number gain or overexpression of MMP‐16 has been determined as a putative indicator of adverse melanoma prognosis, associated with poor clinical outcome, collagen bundle assembly around tumor cell nests, and lymphatic invasion (Tatti et al, ). Other studies have shown that tumor growth factor beta 1 can increase the levels of MMP‐16, eliciting a potential connection with the invasion and metastasis in bladder cancer (Chen et al, ). Some studies investigating the effects of inhibition of the metalloproteinase have reported promising data.…”
Section: Matrix Metalloproteinase‐16mentioning
confidence: 97%
“…These findings suggest and an association between TGF-β1, MMP-16 and epithelial-mesenchymal transition, in the setting of tumor invasion and metastasis in bladder cancer. 152 …”
Section: Special Attributes Of Specific Mmpsmentioning
confidence: 99%
“…According to another study, miR-200b targets and inhibits the expression of MMP16. TGF-β1-mediated repression miR-200b leads to activation of MMP16 expression and stimulation of the migration of bladder cancer cells [297]. TGF-β1-induced expression of oncogenic miR-221 triggers EMT and stimulates the migration and invasion of bladder cancer cells [298].…”
Section: Bladder Cancermentioning
confidence: 99%